Accelerated method for solving grid equations II (3 – D case) - A, Dang Quang (Journal of Computer Science and Cybernetics, 2016)
In this paper following the parametric extrapolation technique [1] we consider the case when the starting operator is split into the sum of  three operators. A result on estimating iteration numbers needed for solving the perturbed problem is  obtained. Finally, the advantage of  our method over the direct use of  the alternating directions method is shown on examples.